Medical centers location and specialists’ allocation: a healthcare planning case study - João Flávio de Freitas Almeida; Luiz Ricardo Pinto; Samuel Vieira Conceição; Francisco Carlos Cardoso de Campos (Production)
Abstract Paper aims To set the locations of new medical centers to meet the population’s secondary care needs, the additional number of specialists, equipment, and an installation sequence at municipalities. Originality We developed descriptive cost functions models and adopted aggregate data from official sources to set parameters of an integrated MILP model. Research method A case study at the Brazilian state of Minas Gerais. Main findings For every scenario, the recommended locations set centers dispersed over the state area, in cities with the minimum required infrastructure. We also propose a scenario of secondary care network re-design and demonstrate the reduced cost of such a strategy. Implications for theory and practice To automate the decision process, we developed a web-based system, providing flexibility and scientific-based results. Finally, we propose a sequence for installing 43 new medical centers and improving the capacity of 27 existing infrastructure based on equality principles.